2004
DOI: 10.1002/jsfa.1893
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo digestibility of the albumin and globulin fractions of eight Brazilian cowpea [Vigna unguiculata (L) Walp] cultivars

Abstract: Cowpea (Vigna unguiculata) is a very important crop for people living in the north-east of Brazilwhere it constitutes the principal source of protein and carbohydrate. In this study, it was observed that the in vitro digestibility of the seed albumin and globulin fractions extracted from eight Brazilian cowpea cultivars was high when treated with pepsin but resistant to degradation by trypsin or chymotrypsin even after 3 h of treatment. When the albumin and globulin fractions were given to rats by intragastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…PD increased considerably up to 24 h soaking in case of chick pea, whereas increasing trend was noticed up to 36 h soaking in case of pigeon pea. Oliveira et al . (2004) observed that the in vitro digestibility of the seed albumin and globulin fractions extracted from eight Brazilian cow pea cultivars was high when treated with pepsin but resistant to degradation by trypsin or chymotrypsin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PD increased considerably up to 24 h soaking in case of chick pea, whereas increasing trend was noticed up to 36 h soaking in case of pigeon pea. Oliveira et al . (2004) observed that the in vitro digestibility of the seed albumin and globulin fractions extracted from eight Brazilian cow pea cultivars was high when treated with pepsin but resistant to degradation by trypsin or chymotrypsin.…”
Section: Discussionmentioning
confidence: 99%
“…For assessing protein quality in vitro and in vivo methods are employed. Present studies on IVPD have been worked out by various investigators by using proteolytic enzymes (Sarwar, 1997; Oliveira et al ., 2004; Urbano et al ., 2005a, b). Laurena et al ., (1991) studied IVPD’s of various legumes and reported a range of 70–90% where multienzyme system was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of data complexity promotes better observation of possible (2022) 4:16 connections between variables. Previous studies have also shown that there may be variations in protein fractions among different cultivars (Oliveira et al 2004;Teka et al 2020;I. M. Vasconcelos et al 2010).…”
Section: Comparison Of Protein Profilementioning
confidence: 91%